Mid-crustal reactivation processes linked to frictional melting and deep void development during seismogenic slip: examples from the Lewisian Complex, NW Scotland. Issue 2 (2023) - Hardman, K.; Holdsworth, R. E.; Scott, L.; Dempsey, E.; McCaffrey, K. J. W.
No abstract available